ASPEK SOSIAL DALAM NASKAH DRAMA SUNDA “RINGKANG PEUTING” KARYA ROSYID E. ABBY - Munif , Muhamad (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2018)
This research aims to describe the elements of the script builder Ringkang Peuting saduran Rosiyd E. Abby and also reveal the social aspects contained as objects. This research uses a sociological approach to literature with the method used is content analysis. The data source comes from the play. Based on analysis, play script. The character is contained in the play, there are 8 characters, namely the main character Ningsih, the round character Mamih, the simple figure Somad and others as supporting characters. It can be concluded that based on the structure of the play and the social aspects contained in Rosiyd É's "Ringkang Peuting". Abby can enrich Sundanese literature, especially plays.